Studying stability of CFRP composites to low-energy impact damage by laser vibrometry; Russian Journal of Nondestructive Testing; Vol. 55, iss. 9 - Shpilnoy V. Yu. Viktor Yurjevich; Vavilov V. P. Vladimir Platonovich; Derusova D. A. Dariya Aleksandrovna; Krasnoveykin V. A. Vladimir Alekseevich (2019, 2019)
Title screen